Prevalence and Genetic Diversity of Torque Teno Sus Viruses 1 and 2 in Pigs in Chiang Mai and Lamphun, Thailand - Saekhow, Prayuth; Chupia, Vena (Journal of Mahanakorn Veterinary Medicine, 2019)
Torque teno sus viruses 1 and 2 (TTSuV1 and 2) belong to the family Anelloviridae, which is known to commonly infect pigs; however, their pathogenesis is unclear. Studies of TTSuV1 and TTSuV2 in pigs worldwide, especially with regard to their prevalence and genetic diversity, have been conducted; however, the prevalence and genetic diversity of both viruses have not been studied in Chiang Mai and Lamphun, Thailand. Therefore, this study aimed to investigate both viruses in terms of their prevalence and genetic diversity using polymerase chain reaction with specific primers in the tonsils of 100 apparently clinically healthy pigs that are being raised in this region. Overall, the prevalence rates of TTSuV1, TTSuV2, and both in combination, in the pigs were 62% (62/100), 68% (68/100), and 50% (50/100), respectively. Phylogenetic analysis of 5’ untranslated regions of 19 nucleotide sequences of both viruses was conducted. Both viruses were separated into 2 groups. The first group displayed a lack of geographic clustering because the nucleotide sequences in these groups showed extreme differences (TTSuV1 minimum nucleotide sequence identity was recorded at 87% and TTSuV1 minimum nucleotide sequence identity was recorded at 85%). The second group revealed the identical nucleotide sequences as no differences were observed in terms of the nucleotide sequences among the specimens. Our data indicate that the nucleotide sequences of TTSuV1s and s that were detected in Chiang Mai and Lamphun, Thailand, likely were adapted from their genome.